Hazard consistent record selection procedures accounting for horizontal and vertical components of the ground motion: Application to liquid storage tanks. (17th January 2023) - Kohrangi, Mohsen; Bakalis, Konstantinos; Triantafyllou, Georgios; Vamvatsikos, Dimitrios; Bazzurro, Paolo
Abstract: A methodology is proposed to enable state‐of‐the‐art record selection using ground motion components in all three principal loading directions. Relying on the well‐established Conditional Spectrum approach, its fundamental concepts are extended to ensure hazard consistency when the vertical ground motion component is considered along with the horizontal ones. To this end, different record selection techniques are employed, spanning sets of ground motion records with and without vertical motions, as well as with and without vertical ground motion hazard consistency. To demonstrate the effect that each record set can potentially have on a structure, an unanchored liquid storage tank is adopted as a case study, because of the vertical uplift motion it can exhibit, even under the application of horizontal loading only. A reduced‐order structural model is employed to generate the numerical output via multi‐stripe analysis, thus enabling the evaluation of the pertinent record selection approaches. Focusing on uplift and compressive meridional stress, response ratios and response hazard curves are extracted. It is shown that although the vertical ground motion component only mildly affects uplift, its effect on compressive meridional stress, on average, amplifies the response by a factor of 1.8 for moderate intensities and 2.8 for higher ones. Accounting for hazard consistency in the vertical component appears to be important for the case at hand, as it reveals notable discrepancies in the mean annual frequency of exceedance for the response parameters examined.